2023
DOI: 10.2147/jir.s419994
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of SLC35A2 in Pan-Cancer and Validation of Its Role in Breast Cancer

Abstract: Purpose Elucidation of the oncogenic role of SLC35A2 in human tumors and the potential function and clinical significance in breast cancer. Methods Pan-cancer analysis was performed via various bioinformatics tools to explain the pathogenic role of SLC35A2. A prognostic nomogram was also developed based on the SLC35A2 expression and clinicopathological characteristics in breast cancer patients. In addition, the role of SLC35A2 was validated in breast cancer by in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Similar to our results, Sun et al . [22] reported that elevated expression of SLC35A2 could promote breast cancer cell proliferation, migration, invasion and epithelial–mesenchymal transition. However, Liu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, Sun et al . [22] reported that elevated expression of SLC35A2 could promote breast cancer cell proliferation, migration, invasion and epithelial–mesenchymal transition. However, Liu et al .…”
Section: Discussionmentioning
confidence: 99%